Subcommittee on Accounting by Debtors and Creditors of the Committee on Financial Accounting Standards. (The Accounting Review, 1977)
Abstract This article presents the text of a report by an American Accounting Association subcommittee on accounting by debtors and creditors during cases of debt restructuring in the U.S. as of October 2, 1977. The subcommittee believes that statement users must compare statement data with similar data from several prior periods and with similar data from the reports of other firms of the current and several prior periods to make rational decisions related to firm valuation and/or management evaluation. Thus, statement data from period to period and from firm to firm must be comparable. Data are comparable when their rational use yields decisions in accord with reality. The mere use of identical accounting procedures from period to period or firm to firm does not assure comparable data. The subcommittee believes that explicit recognition of at least certain characteristics of the appropriate concept of net income is crucial to the resolution of the problems resulting from debt restructuring. It is apparent that, over the life of a firm, accounting statements report and statement users believe that net income results whenever more cash is received than is disbursed after adjusting for investments and disinvestments of the firm owners.